Development of an App for Estimating Criteria for Net Zero Building Based on the Passive House Standard: ÁBita - Gonzalez Cera, Gabriel Yoel; Villegas Perez, Aimee Alejandra; Echegaray Gonzalez, Jorge; López Leyva, Josué Aarón (My University, 2026)
This paper presents Ábita, a novel mobile application developed to estimate compliance with the Passive House standard and target Net Zero Energy goals in the Mexican residential sector. The technical contribution is an iOS tool built with SwiftUI and an MVVM architecture featuring a specialized calculation engine that verifies key parameters, such as heating demand, cooling load, and airtightness, against official criteria. From a scientific standpoint, the tool translates complex energy modeling into an accessible platform and addresses a gap in pre-certification tools for regions with limited certifiers. Future work will focus on validating the calculation algorithms with real building data and expanding to Android. The project aims to promote sustainability by making the design of highperformance, energy-efficient buildings more accessible.
IEEE Conference on Technologies for Sustainability
Keywords: Energy; Modeling; buildings; standards; Design methodology; printing; tools; Energy consumption; modules (abstract algebra); loading; Campus Ensenada